Prototype of Safety System Monitoring on Komatsu PC 200-7 Excavator Using Microcontroller - Pratama, Dio Wahyu; Ariandi, Muhamad (Program Studi Teknik Elektro Universitas Khairun, 2024)
PC200-7 Excavator is a type of excavator that still does not have an effective and efficient safety system monitoring in knowing the oil level and overheating that occurs. Given this, researchers designed and made a prototype of a tool that could later be applied to the excavator industry, by adding several sensor components such as ultrasonics and thermocouples that are useful for checking hydraulic oil levels so that drivers do not struggle to check manually and check the temperature on the engine to avoid overheating by setting a normal temperature height limit. If it exceeds the normal temperature limit, the engine of the excavator will die. To prevent damage to the engine, the temperature on the prototype was made a limit of 40 oC. If there is a human behind the excavator, it will be detected with a distance of 200 cm by the ultrasonic sensor. So that the results obtained are able to monitor the oil level, if less than the specified limit of 3cm, and the temperature on the engine will be automatically detected if the engine temperature is above 40 oC automatically turns off and gives a warning to the driver in the cabin in the form of a writing message and sound from the buzzer. For the detection of human objects behind the excavator will be active if there is a human object with a distance of less than 200 cm, then the buzzer will turn on, then give a notification writing on the LCD in the cabin and the excavator will stop, but the engine still starts. In this research method, measurements and calculations will then be compared with Â datasheets. Calculation results were obtained for Ultrasonic sensors 5.16 VDC, for Thermocouple sensors 3.148 VDC. and for RFID 3.278 VDC